Isolation of endophytic bacteria and fungi from soursop (Annona muricata L.) and bioactivity test as antimicrobial against Eschericia coli, Staphylococcus epidermidis, and Candida albicans - Nurul Aisyah; Lalu Zulkifli; Dewa Ayu Citra Rasmi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
This study aimed to test the antimicrobial activity of endophytic bacteria and fungi isolates of soursop (Annona muricata L.) in inhibiting the growth of E.coli, S. epidermidis, and C. albicans. The stages of the research were the isolation of endophytic bacteria, antimicrobial assay, and characterization of potential endophytic bacteria and fungi. Endophytic microbial was isolated from leaves, bark, and root of soursop taken from Praya, Central Lombok. The agar diffusion method was used in the antimicrobial activity assay. Characterization was carried out on endophytic microbes with antimicrobial activity based on colony morphology, Gram staining, and biochemical tests. The antimicrobial activity test results showed that none of the endophytic bacteria and fungi isolates had intense activity inhibiting the test microbes' growth. Isolates with code DN3, DNX, and AKRX had medium activity against E. coli, isolates with code AKR1 had medium activity against S. epidermidis, and isolates with code DN2 AKRX had medium activity against C.albicans. The research results showed that the endophytic bacteria from soursop plants could inhibit the growth of test microbes in the weak to moderate.